2013
DOI: 10.1002/ijc.28176
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous alpha, beta and gamma human papillomaviruses in relation to squamous cell carcinoma of the skin: A population‐based study

Abstract: Human papillomavirus (HPV) infection is common worldwide and, in immunodeficient populations, may contribute to the pathogenesis of keratinocyte cancers, particularly squamous cell carcinomas (SCC). However, their role in SCC in the general population is less clear. We conducted a comprehensive analysis to investigate the independent effects of seropositivity for cutaneous alpha, beta and gamma HPV types on risk of SCC, and a meta-analysis of the available literature. In a population-based case-control study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 47 publications
(111 reference statements)
3
54
0
Order By: Relevance
“…Seroepidemiological studies have associated skin cancer in organ transplant recipients with the presence of anti-b-HPV antibodies, and PCR-based studies have identified b-HPV DNA in over 80% of skin tumors from these patients. 22,[35][36][37][38][39][40][41][42][43] Despite these findings, a causal role of these viruses has been difficult to verify because of their ubiquitous prevalence in the general population and their absence in some cancers. 25,44 The major weakness of the available studies is that the proposed association is mostly based on the presence of viral DNA in tumor tissues or positive antibody responses.…”
mentioning
confidence: 99%
“…Seroepidemiological studies have associated skin cancer in organ transplant recipients with the presence of anti-b-HPV antibodies, and PCR-based studies have identified b-HPV DNA in over 80% of skin tumors from these patients. 22,[35][36][37][38][39][40][41][42][43] Despite these findings, a causal role of these viruses has been difficult to verify because of their ubiquitous prevalence in the general population and their absence in some cancers. 25,44 The major weakness of the available studies is that the proposed association is mostly based on the presence of viral DNA in tumor tissues or positive antibody responses.…”
mentioning
confidence: 99%
“…βPV‐infected cells may have impaired DNA repair and decreased sensitivity to apoptosis induced by ultraviolet radiation (UVR), facilitating escape from normal cellular defense mechanisms 9, 13. A substantial body of epidemiologic data show an association between HPV infection and cSCC,12, 20, 21, 22, 23, 24 in particular, in OTRs 25, 26. In most studies, HPV infection has been determined by detection of serologic responses to a large series of βPV and sometimes γPV types12, 21, 22, 23, 25, 26, 27, 28, 29, 30, 31 and less frequently by detecting genomic DNA from 1 or multiple HPV types in eyebrow hair or skin scrapings 20, 21, 25, 32, 33, 34…”
Section: Introductionmentioning
confidence: 99%
“…Case‐control studies in both OTR and immunocompetent populations have shown that the presence of βPV DNA or antibodies was associated with a 1.5‐ to 3‐fold increased risk of cSCC 12, 20, 21, 22, 23, 24, 25, 26, 29, 31, 32. It was not possible, however, to determine whether the βPV infection increases risk of cSCC development or whether cSCC formation promotes active proliferation of βPV.…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous β-HPVs are associated with SCCs in patients with the autosomal recessive disorder epidermodysplasia verruciformis (EV) (Gewirtzman et al, 2008). The burden of β-HPV infection predicts risk of subsequent development of SCC (Farzan et al, 2013), and antibodies to β-HPVs, suggesting active HPV infection, are associated with SCC in immunosuppressed patients (Genders et al, 2015). However, transcription of β-HPV RNA is not observed in healthy skin or in premalignant or malignant skin lesions (Arron et al, 2011), supporting a 'hit-and-run' role for β-HPVs in cutaneous carcinogenesis (Pfister, 2003).…”
Section: Introductionmentioning
confidence: 99%